Infection of Human B Lymphocytes with Lymphocryptoviruses Related to Epstein-Barr Virus - Moghaddam, Amir (American Society for Microbiology, 1998)
Lymphocryptoviruses (LCVs) naturally infecting Old World nonhuman primates are closely related to the human LCV, Epstein-Barr virus (EBV), and share similar genome organization and sequences, biologic properties, epidemiology, and pathogenesis. LCVs can efficiently immortalize B lymphocytes from the autologous species, but the ability of a given LCV to immortalize B cells from other Old World primate species is variable. We found that LCV from rhesus monkeys did not immortalize human B cells, and EBV did not immortalize rhesus monkey B cells. In this study, baboon LCV could not immortalize human peripheral blood B cells but could readily immortalize rhesus monkey B cells. Thus, efficient LCV-induced B-cell immortalization across distant Old World primate species appears to be restricted by a species-specific block. To further characterize this species restriction, we first cloned the rhesus monkey LCV major membrane glycoprotein and discovered that the binding epitope for the EBV receptor, CD21, was highly conserved. Stable infections of human B cells with recombinant amplicons packaged in rhesus monkey or baboon LCV envelopes were also consistent with a species-restricted block occurring after virus binding and penetration. Transient infections of human B cells with simian LCV resulted in latent LCV EBNA-2 gene expression and activation of cell CD23 gene expression. EBV-immortalized human B cells could be coinfected with baboon LCV, and the simian virus persisted and replicated in human B cells. Thus, several lines of evidence indicate that the species restriction for efficient LCV-induced B-cell immortalization occurs beyond virus binding and penetration. This has important implications for the study of LCV infection in Old World primate models and for human xenotransplantation where simian LCVs may be inadvertently introduced into humans.